Influence of defects on the enhancement of thermoelectric properties in Sn-doped ZnO nanostructure synthesized via hydrothermal route - Arif, Danish; Khan, Rajwali; Abid, Adeel Younas; Safeen, Kashif; Ali, Adnan; Amin, Mohammed A.; Akram, Khizra; Khan, Kamal Hussain; Ali, Zulfiqar; Safeen, Akif (Frontiers in Chemistry, 2025)
The efficiency of materials’ thermoelectric properties is often limited by various factors, and enhancing these properties through defect engineering is an effective strategy. This study investigated the defects-induced thermoelectric characteristics of Sn-doped ZnO nanoparticles. The samples were synthesized using the hydrothermal technique with varying concentrations of Sn. X-ray diffraction analysis confirmed that pure and Sn-doped ZnO nanoparticles exhibit a wurtzite structure, with an average crystallite size ranging from 22.8 to 18.1 nm. SEM micrographs revealed rod-like morphology which changes into spherical and irregular morphologies across all samples, with increased agglomeration observed with doping. EDX analysis verified the Sn incorporation into Sn-doped ZnO nanostructure. The photoluminescence (PL) spectrum showed significantly enhanced green emission, attributed to an increase in defect concentrations with doping. The electrical conductivity is increased with doping while the Seebeck coefficient reached the highest value of 166 μV/K for the SZ-2 sample, which is higher than any other synthesized sample. This behavior of the thermoelectric properties can be attributed to the presumable increased free carrier density induced by Sn doping in the ZnO crystal lattice, which enhanced both the Seebeck coefficient and electrical conductivity, thereby improving thermoelectric efficiency.